Prevalence of Temporomandibular Joint Disorders among Yemeni University students: A prospective, cross-sectional study - Al-sanabani JS; Al-Moraissi EA; Almaweri AA (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Purpose: The aim of this study was to estimate prevalence of temporomandibular Joint disorders (TMDs), among dental university student in Yemen. Material and methods: A prospective cross-sectional study was conducted in the Department of Oral Medicine and Oral Diagnosis, Faculty of Dentistry, Thamar University, Yemen. Study sample consisted of 207 university students (114 males and 93 females). Predictor's variables were age, gender and marital status. The outcomes variables were the signs and symptoms of TMDs using the Helkimo clinical dysfunction (Di) and anamnestic (Ai) indices. Results: The results revealed that prevalence of TMDs among Yemeni dental students was 41.07 % (mild: 14.01%, sever: 27.05%). In the clinical examination, 49.76 % (mild: 20.77%, moderate; 12.08% and sever; 16.91%) showed some degree of dysfunction. Females showed a signifi cant higher prevalence of TMDs than males. There was signifi cant association between the dysfunction of TMD and gender (P > 0.005). Conclusion: The result of this study showed that prevalence of TMDs among Yemeni dental students was higher than some studies have reported in the literature. Also, the results revealed that majority of studied sample were not aware of the presence of their TMD.